Kajian Inovasi Sektor Usaha Kecil Menengah (UKM) dengan Pendekatan Sistem Dinamis - Trisnawati Trisnawati (Politeknik Negeri Batam, 2016)
The position of SME’s are in the lowest position in the economic structure of the country, but many contribute revenue to the state. The level of competition is very high in SMEs with intense competition. Many emerging SMEs, but many who later went bankrupt. To increase the level of competition in a competitive SME it is necessary to look at the whole situation with the innovation system approach. This study was conducted within three (3) years with the achievements that have been determined each year of data collection, problematization, which tries to simulate the making, represents the real world research data. Based on the results obtained in the first stage is primarily on problem recognition stage by researchers obtained several related things: (a) aspects of the organization, (b) aspects of the institution, (c) aspects of the functions; (d) aspects of the function of the activity, and (e) aspects of the dynamics of organizations, institutions, functions, and activities.